André Scrima’s contribution to the ecumenical break through in Orthodox-Catholic relationships: a historical reconstruction (1957-1967) - Coman, Viorel ca. 20./21. Jh. (Orientalia christiana periodica, 2020)
The article focuses on the contribution of the Romanian Orthodox theologian André Scrima (1925-2000) to the ecumenical turn in Orthodox-Catholic relationships. Scrima was the personal representative of the Ecumenical Patriarch Athenagoras I to Vatican II (1962-1965), and a key figure in the process that led Constantinople and Rome from estrangement to conversation and cooperation in the 1960s. Most of the scholarship that explores the Orthodox impetus to this turn to dialogue focuses almost exclusively on the ecumenical initiatives of the representatives of the Russian diaspora in Paris. That being the case, no solid attention is given to Scrima’s role in the breaking down of the long heritage of division between Orthodoxy and Catholicism. Drawing on unexplored archival material, this article fills this lacuna, offering an analysis of Scrima’s contribution to the ecumenical turn in Orthodox-Catholic relationships during the time period between 1957 and 1967. In so doing, the article reconstructs the key role played by the Romanian theologian in the events that changed the trajectory of Orthodox-Catholic relationships.